Preparation method of silicon carbon material for negative electrode of lithium ion battery
Silicon is deposited by vacuum impregnation and solvent thermal method, and then high-temperature thermal cracking and coated carbon is carried out to prepare high-quality silicon carbon materials, which solves the problem of improving the energy density and cycle life of the negative electrode material of lithium-ion batteries and achieves better electrochemical performance.
Patent Information
- Application Number
- CN202411881375.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-25
AI Technical Summary
There is room for improvement in the energy density and cycle life of existing lithium-ion battery anode materials, especially the complex preparation methods of silicon-carbon anode materials, resulting in limited mass production and marketing promotion.
The dual impregnation treatment of porous carbon and silicon source solution in a vacuum environment was adopted, silicon was deposited in combination with solvent thermal method, and carbon was coated by high-temperature thermal cracking, and finally obtained a silicon carbon material suitable for the negative electrode of lithium-ion batteries through grinding and refining.
It significantly improves the energy density and cycle life of the negative electrode material of lithium-ion battery, improves its rate performance, and meets the needs of high energy density, long cycle life and high rate charge and discharge.
Smart Images

Figure CN119683604A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a method for preparing a silicon-carbon material for a negative electrode of a lithium ion battery. Background Art
[0002] In the field of new energy batteries, lithium-ion batteries have become the protagonist of new energy batteries due to their high energy density and fast charging speed. They play a leading role in the field of electric vehicles, shoulder the burden of energy storage and dual carbon, and form a new industrial chain.
[0003] Positive electrode materials, negative electrode materials, electrolytes, and separators are the four core materials of lithium-ion batteries. The current negative electrode of lithium-ion batteries uses graphite electrodes, and the highest theoretical specific capacity is 370mAh / g. At present, lithium-ion batteries are close to the limit of graphite electrodes and there is no room for improvement. On the other hand, the theoretical capacity density of silicon negative electrodes is 4200mAh / g, which is 10 times that of graphite negative electrodes. The lithium insertion potential of silicon is higher than that of carbon, and its safety performance is better, but silicon has poor conductivity. During the lithium ion insertion and extraction process, the volume change of silicon electrodes reaches 360%, resulting in material crushing and structural collapse, and the destruction of ion and conductivity channels, which limits the application of silicon in lithium-ion batteries. Researchers have made improvements to the defects of silicon itself, such as preparing nano-silicon particles, nano-sheets, nano-porous structures, etc. Although the volume expansion of silicon negative electrodes has been reduced to a certain extent, a longer cycle life than large particles has been obtained, but serious capacity decay still occurs after 20 cycles. Therefore, in response to the shortcomings of silicon negative electrodes, researchers have studied composite materials of silicon and carbon. Carbon has good conductivity. Mixed grinding or sintering of silicon and carbon can make up for the poor conductivity of silicon when it is used alone as an electrode active material. At the same time, carbon materials can alleviate the problem of silicon expansion and improve the breakage and reorganization of silicon electrodes.
[0004] At present, countries around the world are competing to develop silicon-carbon electrodes. The most commonly used method for preparing silicon-carbon is the technology developed by Group-14 in the United States. Silane is used as the silicon source, and silicon is deposited in porous carbon at a high temperature of more than 800°C by chemical vapor deposition (CVD). Then, a carbon source gas (such as methane, acetylene, etc.) is used at high temperature to coat the carbon layer on the outside of silicon nanoparticles through CVD reaction to form a C-Si-C structured silicon-carbon negative electrode material. Due to the complexity of the manufacturing technology, it is still an obstacle to the manufacture of silicon-carbon negative electrodes for lithium-ion batteries, and has become a bottleneck for the mass production and market entry of silicon-carbon negative electrodes.
[0005] When using Group-14's technology to manufacture silicon-carbon negative electrode materials, the following technical points need to be noted: (1) Select porous carbon with a suitable pore structure as the substrate; (2) Use an appropriate silicon source gas (usually silane) to perform a vapor deposition (CVD) reaction in the porous carbon at high temperature; (3) Select an appropriate carbon source gas to thermally decompose at high temperature to coat carbon on the silicon particles. In actual operation, the following technical difficulties may be encountered: (a) The structure of the porous carbon substrate is not hard enough to withstand the tension caused by the expansion of silicon particles; (b) The speed of the vapor deposition reaction using silane at high temperature (800-1000℃) is very fast, and the size of the silicon crystal particles and the amount of deposited silicon are difficult to control, and the operation is very dangerous. (c) It is impossible to ensure that silane gas enters the pores of porous carbon for deposition reaction at high temperature; (d) When carbonizing and coating carbon outside silicon particles at high temperature, it is difficult for methane, acetylene and other gases to enter the pores of porous carbon at high temperature and accurately cover the surface of silicon crystal particles; (e) It is difficult to control the amount of silicon and carbon in both CVD deposition of silicon and high-temperature thermal cracking coating of carbon. These technical difficulties hinder the quality improvement and mass production of silicon-carbon negative electrode materials for lithium-ion batteries. Summary of the invention
[0006] In view of this, an object of the present invention is to provide a method for preparing a silicon-carbon material for a negative electrode of a lithium ion battery.
[0007] The objective of the present invention is achieved through the following technical solutions:
[0008] <First aspect>
[0009] The present invention provides a method for preparing a silicon-carbon material, comprising the following steps:
[0010] S1. In a vacuum environment, placing the porous carbon in a silicon source solution for a first impregnation treatment, filtering and separating, and washing the surface of the porous carbon with an organic solvent to obtain a first impregnation material;
[0011] S2, subjecting the first impregnation material to pressurized solvent thermal treatment, separating the solid product, and obtaining a porous carbon material with deposited silicon;
[0012] S3, placing the silicon-deposited porous carbon material in a carbon source solvent for a second impregnation treatment under a vacuum environment to obtain a second impregnation material;
[0013] S4, performing thermal cracking treatment on the second impregnation material under a protective atmosphere to obtain a carbon-coated silicon-carbon material;
[0014] S5, grinding and refining the carbon-coated silicon-carbon material to obtain a silicon-carbon material for a negative electrode of a lithium-ion battery;
[0015] The silicon source solution is an organic solution containing a silicon source solute and an organic solvent, the silicon source solute is one or more of polycarbonate, monosilane, disilane, tetramethylsilane, tetraethylsilane, tetrafluorosilane, chlorosilane, trichlorosilane, and phenylsilane, and the organic solvent is one or more of n-hexane, cyclohexane, benzene, phenol, gasoline, solvent oil, and kerosene; the carbon source solution is one or more of n-hexane, cyclohexane, carbon disulfide, tetrahydrofuran, chloroform, benzene, phenol, gasoline, solvent oil, and kerosene.
[0016] As an embodiment, the silicon source solution also includes organic matter containing nitrogen, sulfur and phosphorus as doping solutes.
[0017] In some embodiments, the silicon source solution further includes urea.
[0018] As an embodiment, the porous carbon is resin-derived hard carbon, lignin-derived hard carbon, coconut shell-derived hard carbon or hard carbon from other sources, obtained through appropriate activation treatment.
[0019] As an embodiment, the porous carbon has a pore volume of ≥0.8 mL / g, a pore volume of >1600 m 2 / g of specific surface area, of which the micropore volume is ≥0.5mL / g and the mesopore volume is ≥0.2mL / g.
[0020] As an embodiment, more than 85% of the pores in the porous carbon are micropores with a pore size of 0.5 to 2 nm.
[0021] As an embodiment, the proportion of mesopores with a pore size of 2 to 5 nm in the porous carbon is between 10 and 15%.
[0022] As an embodiment, the porous carbon has a total pore volume of 0.8 to 4.5 mL / g.
[0023] In some embodiments, the porous carbon has a total pore volume of 4.1-4.2 mL / g.
[0024] As an embodiment, the specific surface area of the porous carbon is greater than 2000m 2 / g.
[0025] In some embodiments, the specific surface area of the porous carbon is between 2100 and 2200 m 2 / g.
[0026] As an embodiment, the porous carbon includes graphene microcrystalline structures.
[0027] As an embodiment, the porous carbon includes graphene microcrystalline structures of 3 to 5 nm.
[0028] As an embodiment, the porous carbon includes 3 to 5 layers of graphene microcrystalline structure.
[0029] As an embodiment, the median particle size D of the porous carbon is 50 Between 5 and 9 microns.
[0030] In some embodiments, the median particle size D of the porous carbon is 50 5 microns.
[0031] As an embodiment, the organic solvent and the carbon source solvent are the same substance.
[0032] In some embodiments, the silicon source solute in the silicon source solution is tetraethylsilane, and the solvent is gasoline; the carbon source solvent is gasoline.
[0033] As an embodiment, in step S1, before the first impregnation treatment, the porous carbon is degassed under vacuum.
[0034] As an embodiment, the mass ratio of the porous carbon to the silicon source solution is 1:(610).
[0035] In some embodiments, the mass ratio of the porous carbon to the silicon source solution is 1:8.
[0036] As an embodiment, in step S2, the parameters of the pressurized solvent thermal treatment are: keeping warm for 1.5 to 4 hours at a temperature of 200 to 250° C. and a pressure of 1.5 to 2.5 mPa.
[0037] As an embodiment, the parameters in the degassing treatment or the first impregnation treatment or the second impregnation treatment are: vacuum degree is -0.07 to -0.1 mPa, and the treatment time is 25 to 40 minutes.
[0038] In some embodiments, in step S1, the vacuum degree of the degassing treatment, the first immersion treatment, and the second immersion treatment is -0.08 mPa, and the treatment time is 30 min.
[0039] As an embodiment, in step S4, the temperature of the thermal cracking treatment is 600 to 1200° C. and the time is 1 to 3 hours.
[0040] In some embodiments, the thermal cracking treatment is performed at a temperature of 1000° C. and for a time of 2 hours.
[0041] As an embodiment, in step S5, the grinding and refining is to grind the carbon-coated silicon-carbon material obtained in step S4 to a median particle size D 50 5~9μm.
[0042] In some embodiments, the median particle size D after grinding is 50 8μm.
[0043] <Second Aspect>
[0044] The present invention provides a silicon-carbon material, which is prepared by the above-mentioned method for preparing the silicon-carbon material.
[0045] As an embodiment, the silicon-carbon material is suitable for use in preparing lithium-ion batteries, for preparing negative electrode plates.
[0046] <Third Aspect>
[0047] The present invention provides application of the silicon-carbon material.
[0048] The silicon-carbon material is suitable for use in lithium-ion batteries and is used to prepare negative electrode plates.
[0049] Compared with the prior art, the present invention has the following beneficial effects:
[0050] The present invention uses an organic silicon source solution to vacuum impregnate porous carbon, then uses a solvent thermal method to deposit silicon on the pore surface of the porous carbon, then vacuum impregnates the carbon source solvent into the porous carbon with deposited silicon, then performs high-temperature thermal cracking for carbon coating, and finally grinds and refines to obtain a silicon-carbon material. The prepared silicon-carbon material is suitable for use in the negative electrode of lithium-ion batteries. While increasing the energy density of the negative electrode material of lithium-ion batteries, it significantly improves its cycle life and rate performance, so that the prepared silicon-carbon material has better electrochemical properties and can better meet the application requirements of lithium-ion batteries in high energy density, long cycle life, and high rate charge and discharge. The preparation method has the following advantages:
[0051] (I) Vacuum impregnation of porous carbon with organic silicon source solution to ensure that the silicon source penetrates deeply into the pores of the carbon
[0052] Vacuum impregnation of organic silicon source solution, through a special vacuum impregnation device, ensures that under negative pressure conditions, the silicon source solute goes deep into the pores of porous carbon with the solution, creating conditions for accurate, efficient, quantitative and controllable deposition of silicon. In contrast, it is difficult to ensure that silane accurately enters the pores of porous carbon using chemical vapor deposition.
[0053] (II) Solvent thermal deposition of silicon is safer and more efficient than silane vapor deposition CVD
[0054] After vacuum impregnation of the organic silicon source solution, silicon is deposited by solvent hot liquid phase deposition in a sealed high-pressure reactor. This is safe and reliable, and the amount of deposited silicon can be controlled by the concentration of the silicon source organic solution, the impregnation time, and the number of impregnations. In comparison, the operation of using gas silane to deposit in porous carbon by chemical vapor deposition is more dangerous. Gas silane is easy to leak and may burn and explode when it encounters water or air. The particle size and reaction speed in the vapor deposition reaction of silane are difficult to control, and the quality is difficult to guarantee.
[0055] (III) Solvothermal method is easier to achieve silicon-carbon doping reaction than vapor deposition method
[0056] In a solvothermal reaction, the reactants are in a non-aqueous solvent and react under supercritical high temperature and high pressure conditions. The reactants can be effectively dispersed and activated at a relatively low temperature (compared to CVD reactions), thereby promoting the occurrence of reactions and the formation of products. This method is suitable for water-sensitive materials such as III-V semiconductor compounds, nitrides, and chalcogenides, because they are difficult to synthesize in aqueous solutions or are prone to hydrolysis, oxidation, and other reactions. Therefore, the solvothermal method is particularly conducive to the deposition of heteroatoms on carbon materials, and can carry out doping reactions of elements such as nitrogen, phosphorus, and sulfur.
[0057] (IV) Porous carbon deposited by vacuum impregnation of silicon with carbon source solvent achieves the attachment of carbon precursor to silicon particles
[0058] The conventional technology for coating carbon atoms on silicon carbon is to pass carbon source gases such as methane and acetylene into a high-temperature carbonization furnace, where the carbon source organic gas is cracked and carbonized to form a carbon coating layer outside the silicon particles. In actual operation, it is difficult to ensure that gases such as methane and acetylene enter the pores of porous carbon and are accurately coated on the outer layer of silicon particles due to high-temperature gas phase reactions. This patent first performs a vacuum impregnation treatment of the porous carbon deposited with silicon particles with a carbon source solvent, so that the carbon source organic solvent enters the pores of the carbon and is adsorbed on the surface of the silicon particles, and then performs a high-temperature carbonization reaction at 600°C to 1200°C to facilitate the formation of a carbon coating layer outside the silicon particles.
[0059] (V) Double impregnation operation is beneficial to reserve space in porous carbon and overcome the problem of silicon volume expansion
[0060] The present invention adopts a double impregnation operation of the porous carbon with a silicon source solution and a carbon source solvent, which is conducive to reserving space in the pores of the porous carbon, adapting to the volume change caused by the embedding and removal of lithium ions in silicon, and solving the problem of silicon volume expansion. In addition, the double impregnation operation of the silicon source solution and the carbon source solvent is conducive to forming a C-Si-C surface-to-surface bonding structure, and the volume expansion of silicon particles in the vertical direction has a small scale change. In addition, the use of hard porous carbon greatly alleviates the problem of silicon volume expansion.
[0061] (VI) Controlling doping atoms
[0062] Solvothermal reaction is carried out at high temperature and high pressure in the supercritical state of organic solvents. It is suitable for water-sensitive materials, such as III-V semiconductor compounds, nitrides, chalcogenides, etc., because these materials are difficult to synthesize in aqueous solution or are prone to hydrolysis, oxidation and other reactions. In actual implementation, various auxiliary reagents, such as urea and other phosphorus and sulfur-containing reagents, can be added during the two impregnation processes to generate silicon-carbon porous carbon doped with nitrogen, phosphorus and sulfur, and the pseudocapacitance characteristics generated by heteroatoms can be used to adsorb more lithium ions and improve the energy density of lithium-ion batteries.
[0063] In summary, the preparation method of silicon-carbon material provided by the present invention can control product quality in multiple links such as solution concentration, raw material ratio, impregnation time and number of impregnations, and generate high-quality porous carbon-based negative electrode silicon-carbon material. BRIEF DESCRIPTION OF THE DRAWINGS
[0064] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0065] Figure 1 A flow chart of the method for preparing the silicon-carbon material provided by the present invention;
[0066] Figure 2 This is a partial screenshot of the gas phase adsorption test report of the porous carbon used in the embodiments of the present invention;
[0067] Figure 3 This is a high-resolution transmission electron microscopy (HR-TEM) photograph of lignin-based hard carbon in an embodiment of the present invention;
[0068] Figure 4 Schematic diagram of a vacuum suction device for immersion treatment used in an embodiment of the present invention;
[0069] Figure 5 This is a photo of the deposited silicon porous carbon prepared after solvent thermal treatment in Example 1 of the present invention;
[0070] Figure 6 This is a scanning electron microscope (SEM) photograph of the silicon-carbon material prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0071] The present invention is described in detail below in conjunction with embodiments. The following embodiments will help those skilled in the art to further understand the present invention, but are not intended to limit the present invention in any form. It should be noted that, for those of ordinary skill in the art, some adjustments and improvements can also be made without departing from the concept of the present invention. These all belong to the protection scope of the present invention.
[0072] This specific embodiment provides a method for preparing silicon-carbon material for lithium-ion battery negative electrode, which adopts two vacuum liquid phase impregnations, solvent thermal deposition of silicon and high temperature cracking and coating carbon, and sequentially deposits silicon layer and coating carbon layer on the porous carbon material. The raw materials involved include: porous carbon material, silicon source solution and carbon source solution, wherein the base material is porous carbon; the silicon source solution is an organic solution containing silicon source solute; and the carbon source solution is an organic solvent containing C element.
[0073] like Figure 1 As shown, the preparation steps of the silicon-carbon material for the negative electrode are:
[0074] S1. Under vacuum environment, placing porous carbon in a silicon source solution for a first impregnation treatment to obtain a first impregnation material;
[0075] S2, subjecting the first impregnation material to pressurized solvent thermal treatment, and after completion, separating the solid product to obtain a porous carbon material with deposited silicon;
[0076] S3, placing the silicon-deposited porous carbon material in a carbon source solvent for a second impregnation treatment under a vacuum environment to obtain a second impregnation material;
[0077] S4, subjecting the second impregnation material to high-temperature thermal cracking treatment under a protective atmosphere to obtain a carbon-coated silicon-carbon material;
[0078] S5. Grind and refine the carbon-coated silicon-carbon material to obtain a silicon-carbon material for a negative electrode.
[0079] The porous carbon is hard carbon derived from resin, lignin, coconut shell or other sources, obtained by proper activation treatment. For example, lignin-based porous carbon can be prepared by using lignin separated from papermaking black liquor as raw material and potassium carbonate and urea as activators.
[0080] Porous carbon needs to have appropriate pore volume (above 0.8 ml / g), specific surface area (1600 m 2 / g or more), and have a sufficient proportion of micro-mesopores (micropore diameter is less than 2nm, mesopore diameter is 2-5nm, micropore volume ≥0.5mL / g, mesopore volume ≥0.2mL / g).
[0081] The preparation method of the above silicon-carbon material is specifically introduced below through examples.
[0082] Example 1
[0083] The raw materials used in this example are as follows:
[0084] This embodiment specifically uses a lignin-based porous carbon having a graphene microcrystal structure, such as Figure 3As shown in Figure 2, it can be seen that the disordered 3-5 nm graphene microcrystalline structure has 3-5 layers: there are a large number of holes on the surface and a rich hole system inside (such as Figure 2 Specific surface area is 2122m 2 / g, with a total pore volume of 4.126mL / g. There are a large number of micropores with a diameter of 0.5 to 2 nanometers, with a micropore volume of about 0.61mL / g. There are also a large number of mesopores with a diameter of 2 to 5 nanometers, with a mesopore volume of about 0.22mL / g. The median particle size is D 50 =5 microns.
[0085] Silicon source solution: Tetraethylsilane (melting point -82.5°C, boiling point 153-154°C, liquid at room temperature) is used as the solute, gasoline (C4-C12 aliphatic hydrocarbon) is used as the solvent, and the solute and the solvent are prepared in a mass ratio of 1:5 to prepare the silicon source solution.
[0086] Carbon source solution: Gasoline (C4-C12 aliphatic hydrocarbons and cyclic hydrocarbons, such as No. 190 solvent gasoline) is used as the carbon source solution.
[0087] In this embodiment, the steps for preparing the silicon-carbon material are:
[0088] S1. First impregnation treatment
[0089] The vacuum suction device used is as follows Figure 4 As shown, the porous carbon is placed in a conical bottle, the bottle mouth is sealed with a rubber stopper with a gas pipeline and a liquid pipeline, the gas pipeline is connected to a vacuum pump, the liquid pipeline is connected to a silicon source solution, and the gas pipeline and the liquid pipeline are controlled to be on or off by valves.
[0090] S1-1. Place the porous carbon material in a conical flask, close the valve of the liquid pipeline, turn on the vacuum pump, open the valve of the gas pipeline, perform vacuum degassing, and maintain a negative pressure of -0.08 mPa for 30 minutes;
[0091] S1-2. Close the vacuum pump and the gas valve, open the valve of the liquid pipeline, and the silicon source solution is sucked into the container. Then close the valve of the liquid pipeline and immerse the degassed porous carbon for 30 minutes. Use the pressure difference inside and outside the pores to make the silicon source solution penetrate into the pores of the porous carbon.
[0092] In this embodiment, the mass ratio of porous carbon to silicon source solution is 1:8.
[0093] The porous carbon used in this embodiment contains a large number of micropores (<2nm) and some mesopores (2-5nm). The micropores have a large specific surface area due to their small size and extremely abundant number. They play a core and leading role in the adsorption process and can provide many key adsorption sites. The mesopores serve as an important diffusion path for the adsorbate, which effectively promotes the transport and diffusion of the adsorbate within the material, significantly enhances the diffusion efficiency within the particles, and greatly shortens the time consumed for adsorption.
[0094] S2. Operation of depositing silicon in the pores of porous carbon by solvothermal method
[0095] The first impregnation material (a mixture of silicon source solution and porous carbon) is transferred into a high-pressure reactor, the reactor cover is sealed, and then the reactor is placed in a muffle furnace, heated to 220°C at a heating rate of 5°C / min, kept warm for 2 hours, and after power is turned off and cooled to room temperature, the reactor cover is opened, filtered and separated, and the solid matter therein is extracted, thus completing the reaction of solvent thermal deposition of silicon and depositing silicon in the pores of the porous carbon.
[0096] S3. Second dipping treatment
[0097] The porous carbon material with deposited silicon is placed in a conical bottle of a vacuum suction device for vacuum degassing, and a negative pressure of -0.08 mPa is maintained for 30 minutes; the vacuum pump and the gas valve are closed, the valve of the liquid pipeline is opened, the carbon source solution is sucked into the conical bottle, the gas valve is closed, and the second impregnation treatment is performed for 30 minutes, so that the solvent gasoline penetrates into the pores and is coated on the surface of the porous carbon particles with deposited silicon. After the second impregnation treatment is completed, the solvent is filtered and separated to obtain a silicon-containing porous carbon impregnated with a carbon source solution, which is named a silicon-carbon material coated with a carbon source.
[0098] In this embodiment, the mass ratio of the deposited silicon porous carbon to the carbon source solution is 1:5.
[0099] S4. Thermal cracking treatment
[0100] The silicon-carbon material coated with the carbon source is placed in a graphite crucible, put into an atmosphere electric furnace, and heated to 1000°C at a heating rate of 5°C / min under argon protection, and kept warm for 2 hours for high-temperature carbonization to coat a carbon atom layer on the surface of the silicon-carbon material.
[0101] S5. Grinding and refining treatment
[0102] The product obtained in step S4 is ground to D using a jet mill. 50 =8 microns to obtain negative electrode silicon-carbon material.
[0103] like Figure 5 The figure shows the negative electrode silicon-carbon material prepared in this embodiment.
[0104] like Figure 6 , which is a scanning electron microscope image of the negative electrode silicon-carbon material prepared in this embodiment.
[0105] It is worth noting that in the two immersion treatments, after closing the two valves, the conical flask was shaken first to make the mixed solution more uniform, and then allowed to stand.
[0106] In this embodiment, argon is selected as the inert gas.
[0107] Example 2
[0108] The steps of this embodiment are basically the same as those of Embodiment 1, except that:
[0109] In step S2, the solvothermal reaction temperature is increased to 250°C.
[0110] Example 3
[0111] The steps of this embodiment are basically the same as those of Embodiment 1, except that:
[0112] In step S4, the high temperature carbonization temperature is 800°C and kept for 3 hours.
[0113] Example 4
[0114] The steps of this embodiment are basically the same as those of Embodiment 1, except that:
[0115] The silicon source solution also includes urea, the mass of which is three times that of tetraethylsilane, and other parameters remain unchanged.
[0116] Comparative Example 1
[0117] The steps of this comparative example are basically the same as those of Example 1, except that:
[0118] In step S2, the first impregnation material (a mixture of silicon source solution and porous carbon) is transferred into a high-pressure reactor, the solvent thermal reaction temperature is 100° C., and then the reactor is placed in a muffle furnace, and other parameters remain unchanged.
[0119] Comparative Example 2
[0120] The steps of this comparative example are basically the same as those of Example 1, except that:
[0121] In step S2, the first impregnation material (a mixture of silicon source solution and porous carbon) is placed in an atmosphere furnace, and under the protection of inert gas, the temperature is raised to 220° C. and kept for 2 hours, while the other steps remain unchanged.
[0122] Comparative Example 3
[0123] The steps of this comparative example are basically the same as those of Example 1, except that:
[0124] Carbon source solution: replaced with citric acid.
[0125] Test analysis
[0126] The silicon content and conductivity of the silicon-carbon material for the negative electrode prepared in the above Example 1 were measured, wherein the mass content of silicon was tested by ash determination method; the conductivity was measured by powder resistance meter and four-probe method, and the measurement results are listed in Table 1.
[0127] The negative electrode silicon-carbon material, conductive carbon black (Super-P), and binder (SA, 3wt.%) prepared in Example 1 were mixed in a mass ratio of 8:1:1, and water was added to adjust the viscosity to obtain a slurry with moderate viscosity, which was evenly coated on a copper foil and dried in a vacuum environment at 80°C. The negative electrode sheet was then cut to obtain a negative electrode sheet. A CR2032 button battery was assembled in an Ar gas environment. After standing at room temperature for 12 hours, an electrochemical performance test was performed. The battery was charged and discharged at a current of 0.01C to 0.01-1.5V at room temperature, and the constant current charge and discharge capacity was measured. Subsequently, the battery was cycled for 100 cycles at a current of 3C to detect the capacity retention rate and expansion rate. The measurement results are listed in Table 1.
[0128] Table 1 Performance tests of various embodiments and comparative examples
[0129]
[0130] The above describes the specific embodiments of the present invention. It should be understood that the present invention is not limited to the above specific embodiments, and those skilled in the art may make various modifications or variations within the scope of the claims, which do not affect the essence of the present invention.
Claims
1. A method for preparing a silicon-carbon material, characterized in that: The following steps are involved: S1. Under vacuum, the porous carbon is placed in a silicon source solution for a first impregnation treatment, and the first impregnation material is obtained by filtration and separation; S2, subjecting the first impregnation material to pressurized solvent thermal treatment, separating the solid product, and obtaining a porous carbon material with deposited silicon; S3, placing the silicon-deposited porous carbon material in a carbon source solvent for a second impregnation treatment under a vacuum environment to obtain a second impregnation material; S4, subjecting the second impregnation material to high-temperature thermal cracking treatment under a protective atmosphere to obtain a carbon-coated silicon-carbon material; S5, grinding and refining the carbon-coated silicon-carbon material to obtain a silicon-carbon material for a negative electrode of a lithium-ion battery; The silicon source solution is an organic solution containing a silicon source solute and an organic solvent, the silicon source solute is one or more of polycarbonate, monosilane, disilane, tetramethylsilane, tetraethylsilane, tetrafluorosilane, chlorosilane, trichlorosilane, and phenylsilane, and the organic solvent is one or more of n-hexane, cyclohexane, benzene, phenol, gasoline, solvent oil, and kerosene; the carbon source solution is one or more of n-hexane, cyclohexane, carbon disulfide, tetrahydrofuran, chloroform, benzene, phenol, gasoline, solvent oil, and kerosene.
2. The method for preparing the silicon-carbon material according to claim 1, characterized in that: The silicon source solution also includes organic matter containing nitrogen, sulfur and phosphorus as doping solutes.
3. The method for preparing the silicon-carbon material according to claim 1, characterized in that: It also includes one or more of the following technical features: A. The porous carbon is resin-derived hard carbon, lignin-derived hard carbon, coconut shell-derived hard carbon or hard carbon from other sources, obtained by appropriate activation treatment; B. The porous carbon has a pore volume of ≥0.8 mL / g, >1600 m 2 / g specific surface area, of which the micropore volume is ≥0.5mL / g and the mesopore volume is ≥0.2mL / g; C. More than 85% of the porous carbon is micropores of 0.5 to 2 nm; D. The mesopores of 2 to 5 nm in the porous carbon account for between 10 and 15%; E. The porous carbon includes a graphene microcrystalline structure; F. The median particle size D of the porous carbon 50 Between 5 and 9 microns; G. The mass ratio of the porous carbon to the silicon source solution is 1:(6-10).
4. The method for preparing the silicon-carbon material according to claim 1, characterized in that: The organic solvent and the carbon source solution are the same substance.
5. The method for preparing the silicon-carbon material according to claim 1, characterized in that: In step S1, before the first impregnation treatment, the porous carbon is degassed under vacuum.
6. The method for preparing the silicon-carbon material according to claim 1, characterized in that: In step S2, the parameters of the pressurized solvent thermal treatment are: 200-250°C temperature, 1.5-2.5 MPa pressure, and insulation for 1.5-4 hours.
7. The method for preparing the silicon-carbon material according to claim 1, characterized in that: In step S4, the temperature of the thermal cracking treatment is 600-1200° C. and the time is 1-3 hours.
8. The method for preparing the silicon-carbon material according to claim 1, characterized in that: In step S5, the grinding and refinement is to grind the carbon-coated silicon-carbon material obtained in step S4 to a median particle size D 50 5~9μm.
9. A silicon-carbon material, characterized in that: The silicon-carbon material is prepared by the method for preparing the silicon-carbon material according to any one of claims 1 to 8.
10. Use of the silicon-carbon material as claimed in claim 9 in preparing negative electrode sheets for lithium-ion batteries.
Citation Information
Patent Citations
A silicon-carbon composite negative electrode material and a preparation method thereof
CN109004203A
Negative electrode material and preparation method thereof, negative electrode plate, electrochemical device and electronic device
CN114556621A
Silicon-carbon composite material and preparation method thereof, negative active material, negative pole piece, secondary battery and power utilization device
CN116387493A
High-capacity lithium battery negative electrode material and processing technology thereof
CN116706032A
Low-strain silicon-carbon negative electrode material and preparation method and application thereof
CN117317203A
Cited By
Preparation method of vapor deposition silicon carbon material based on supercritical carrier gas
CN120767282A
A method for preparing a silicon-carbon material by vapor deposition based on a supercritical carrier gas
CN120767282B
Preparation method of improved silicon-carbon composite negative electrode material and lithium ion battery
CN120887407A
Preparation method of improved silicon-carbon composite negative electrode material and lithium ion battery
CN120887407B
Preparation method of lignin-based silicon carbon-silicon oxygen negative electrode material
CN121054650A